Pesantrenisasi sebagai Pembentukan Spiritualitas Mahasiswa (Studi Kasus Wajib Lulus BTA-PPI di IAIN Purwokerto) - Hidayat, Arif (Jurnal Penelitian Pendidikan Islam, 2020)
The article attempts to examine about ‘a must to be graduated’ phenomena of al-Qur'an Reading and Writing (BTA) dan The Knowledge of Religious Service Implementation (PPI) at The State Islamic Institute of Purwokerto. This idea may be interesting to review since the materialistic living in global culture has brought anxiety concerning a moral ethics alteration of youth that becomes uncontrolled. From this side, therefore, pesantren (Islamic boarding school) becomes the solution to form spirituality value through BTA-PPI Graduated Compulsory which is programmed educationally by IAIN Purwokerto. Students, who failed BTA-PPI, must "mondok" (be quarantined in a boarding house) until they are really mastered the materials which are able to be carried out well in daily life. As a result, this kind of establishment which is held by BTA-PPI leads the students of IAIN Purwokerto to implement succesfully by knowing tartil and tajwid properly, understanding imla pattern and the importance of Qur'an short verses (juz 30). Related to the knowledge of practicing worship, it may be measured on the fundamental piety/faith, Islam, and ikhsan (elements, requirements, and pillars includedly) that could be implemented to the life of social and nationality.